Kako umestiti tradicijo v sodobnost? - Kerec Prekoršek, Branka (Knjižnica, 2020)
Purpose: In 2018, the Maister Library, held by the University of Maribor library (UKM), became a cultural monument of national importance. It is a comprehensive book heritage, which has been in the possession of the University Library of Maribor since 1998, when a gift agreement was signed with the heirs of General Maister. With the proclamation, the UKM undertook to make a proper inventory of the library materials from Maister’s estate. As this is an extremely personal library, the UKM has endeavored to preserve the original layout as far as possible, both in the layout and in the inventory. This is important not only from the point of view of the preservation and protection of the material itself, but above all for the inventory and presentation of the book legacy of the Maister Library-M maisteriana’s personal book collection as a cultural monument. This preserves the library collection as a whole, and also preserves the principle of provenance and its original arrangement, but with visibility in a reciprocal computer catalog. Methodology/approach: This is a chronological overview of the gradual steps from acquisition to proclamation. In the absence of general instructions or recommendations on how to incorporate original signatures into COBISS, this is an inventory of the processes and decisions that led to the adaptations adopted. This treatment of personal libraries is the exception rather than the rule in this country, as the library profession has not yet recognized the importance of the comprehensive treatment and preserva-tion of personal libraries as cultural and historical assets.Results: The solutions presented for the signing, inventorying and equipping of the material, as well as the incorporation of the existing original layout into the COBISS system in the way required by the rules on the entry of holding data, including the setting of local code lists, show that the incorporation of the original layout is not as simple as it seems at first sight. It brings with it peculiarities that are not quite compatible with the ‘transfer’ to COBISS and its legalities, so the solution presented here is the one that seemed to be the most acceptable in the UKM inventory. The Maister Library at UKM is thus becoming visible in COBIB, while retaining its authentic layout and exceptional character.Research limitations: Personal libraries are a mirror of the individual, not only in terms of their content but also in terms of their classification. These specificities can prove burdensome when trying to transfer the original layout and labelling to an existing inventory system. The latter does not allow all the specificities to be included.Originality/practical implications: The paper presents the organization of work and the inventory procedures, and in particular, explains the structure of the layout and signatures in more detail. The solutions presented may be of help to other personal library administrators who aim to promote the content of the Slovenian mutual catalog more widely through inventorying. The Maister Library at the UKM is an example of systematic treatment of personal library collections. It preserves its authenticity while keeping pace with today’s library profession.
Keywords: knjižne zbirke; kulturna zgodovina; Maister, Rudolf; Maistrova knjižnica; Maribor; osebne knjižnice; Univerzitetna knjižnica; zapuščine